Defence Science Journal from 2007 to 2011: a Bibliometric Study - V Selvavinayagam, A; Muthu, M; Veerachamy, M (International Journal of Engineering and Technology, 2018)
Bibliometrics is the study dealing with written communication used the statistical measurement of the published article. Bibliometrics studies are on the subject of interdisciplinary and major subject in nature of the science and identify the pattern of publication, authorship and citation analysis. This paper is mainly study about Defence Science Journal publications of articles from the period of study 2007 to 2011 only five years. Totally 410 articles published from prescribed periods also described about author wise, year wise, pagination wise of the articles of this journal.Â Â